2017
DOI: 10.18203/2349-2902.isj20174889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of local versus spinal anesthesia in long standing open inguinal hernia repair

Abstract: Background: Hernias are among the oldest known afflictions of human kind and elective inguinal hernia repair is commonly performed operation in general surgery. General or spinal anesthesia are still the most common types of anesthesia being used in India. Studies comparing the recovery profiles of local, general and regional anesthesia show that local anesthesia is ideal for day care surgery.Methods: This study had included 60 cases of male single sided reducible indirect long standing (more than 5 years) ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
4
13
0
Order By: Relevance
“…Urinary retention and headache was observed by Singh, Saxena et al, and Shafique et al in their study. 16,17,24 The occurrence of scrotal swelling was more in local anaesthesia which is similar to the findings by Shafique et al in their study. They observed scrotal swelling was more evident in local anaesthesia i.e.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Urinary retention and headache was observed by Singh, Saxena et al, and Shafique et al in their study. 16,17,24 The occurrence of scrotal swelling was more in local anaesthesia which is similar to the findings by Shafique et al in their study. They observed scrotal swelling was more evident in local anaesthesia i.e.…”
Section: Discussionsupporting
confidence: 89%
“…15 They have concluded that local anaesthesia is better in terms of intra operative pain management but this result is contradicting the findings of Singh. 16 Postoperative pain is the most important variable and the soul of this study. Patient and surgeon satisfaction with acceptability depends upon postoperative pain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study randomly dividing 60 male patients with unilateral inguinal hernia into a group of Lichtenstein repair under local anesthesia and a group with spinal anesthesia, the time spent in local anesthesia was higher [44]. Intraoperative pain was higher in local anesthesia than with spinal anesthesia.…”
Section: Primary Inguinal Hernia Repair In Patients With Severe Cardimentioning
confidence: 94%
“…There was no difference in postoperative pain. Postoperative complications occurred more often in the spinal anesthesia group [44].…”
Section: Primary Inguinal Hernia Repair In Patients With Severe Cardimentioning
confidence: 94%